The clinical efficacy of collagen dressing on chronic wounds: A meta-analysis of 11 randomized controlled trials - Shu, Hongxin; Xia, Zhiyu; Qin, Xuan; Wang, Xiaowei; Lu, Weihang; Luo, Qingyu; Zhang, Zhenxiong; Xiong, Xiaowei (Frontiers in Surgery, 2022)
Objective This study aims to evaluate the clinical efficacy of collagen dressing for patients with chronic wounds. Materials and methods Relevant randomized controlled trials were searched from the databases such as PubMed, EMBASE, and the Cochrane library as of January 2022. For dichotomous outcomes and continuous outcomes, risk ratio and mean difference were calculated, respectively. Subgroup analysis was performed according to the type of chronic ulcer and follow-up. In addition, trial sequential analysis (TSA) was performed to further verify the results. Jadad score was used to assess the quality of trials. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was utilized to assess the level of evidence for outcomes. Results In 11 studies, a total of 961 patients of whom 485 were in the collagen group. Compared with standard of care (SOC) alone, the group that added an extra collagen dressing achieved a higher wound healing rate (Risk Ratio = 1.53; 95% CI, 1.33–1.77). The collagen group also showed a higher healing velocity than the SOC group (Mean Difference, 2.69; 95% CI, 0.87–4.51). In addition, the adverse events related to dressing between the two groups were similar (Risk Ratio = 0.67; 95% CI, 0.44–1.01). Conclusion Collagen dressing increases the wound healing rate and may be an effective and safe treatment for chronic wound management. However, more extensive research shall be conducted to substantiate these results. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=245728, identifier: CRD42021245728.